Robust Controller Design for DFIG based Wind Conversion System using Direct Synthesis Approach - Sarfaraz Nawaz Syed, Dr S.Tara Kalyani (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper deals with the performance checking of an optimally designed PID controller with first order filter (PIDF) connected along the grid-side converter (GSC) in a doubly fed induction generator (DFIG) based wind energy conversion system (WECS). Initially, a relay test is conducted to scale back the upper order model of DFIG system to lower order model with dead time. The main objective of proposed controller to protect the system deterioration under various critical conditions such as external disturbances and parameters variation of DFIG. The PID controller parameters are obtained using the direct synthesis method. A systematic guideline is usually recommended for the choice of the tuning parameter of filter. Ultimately, system performance is tested and compared consistent with tracking, durability, distortion reduction. The method provides a significant improvement in the performance of the closed loop. Kharitonov theorem is used to check the robustness of the system. The simulation results indicate the effective use of proposed method into DFIG system in terms of tracking as well as unwanted distortion. The proposed approach goes further in the control of DFIG and wind energy conversion systems over the other existing methods.